Atomic force microscope adhesion measurements and atomistic molecular dynamics simulations at different humidities - Seppä, J.; Reischl, Bernhard; Sairanen, H.; Korpelainen, V.; Husu, H.; Heinonen, M.; Raiteri, P.; Rohl, Andrew; Nordlund, K.; Lassila, A. (IOP Publishing Ltd, 2017)
Due to their operation principle atomic force microscopes (AFMs) are sensitive to all factors affecting the detected force between the probe and the sample. Relative humidity is an important and often neglected—both in experiments and simulations—factor in the interaction force between AFM probe and sample in air. This paper describes the humidity control system designed and built for the interferometrically traceable metrology AFM (IT-MAFM) at VTT MIKES. The humidity control is based on circulating the air of the AFM enclosure via dryer and humidifier paths with adjustable flow and mixing ratio of dry and humid air. The design humidity range of the system is 20–60 %rh. Force–distance adhesion studies at humidity levels between 25 %rh and 53 %rh are presented and compared to an atomistic molecular dynamics (MD) simulation. The uncertainty level of the thermal noise method implementation used for force constant calibration of the AFM cantilevers is 10 %, being the dominant component of the interaction force measurement uncertainty. Comparing the simulation and the experiment, the primary uncertainties are related to the nominally 7 nm radius and shape of measurement probe apex, possible wear and contamination, and the atomistic simulation technique details. The interaction forces are of the same order of magnitude in simulation and measurement (5 nN). An elongation of a few nanometres of the water meniscus between probe tip and sample, before its rupture, is seen in simulation upon retraction of the tip in higher humidity. This behaviour is also supported by the presented experimental measurement data but the data is insufficient to conclusively verify the quantitative meniscus elongation.